Bond-forming and electron-transfer reactivity between Ar2+ and O2. Issue 16 (8th April 2020) - Armenta Butt, Sam; Price, Stephen D.
Abstract : The reactivity, energetics and dynamics of the bimolecular reactions between Ar 2+ and O2 have been studied using a position sensitive coincidence methodology at a collision energy of 4.4 eV. Abstract : The reactivity, energetics and dynamics of the bimolecular reactions between Ar 2+ and O2 have been studied using a position sensitive coincidence methodology at a collision energy of 4.4 eV. Four bimolecular reaction channels generating pairs of product ions are observed, forming: Ar + + O2 +, Ar + + O +, ArO + + O + and O + + O + . The formation of Ar + + O2 + is a minor channel, involving forward scattering, and generates O2 + in its ground electronic state. This single electron transfer process is expected to be facile by Landau–Zener arguments, but the intensity of this channel is low because the electron transfer pathways involve multi-electron processes. The formation of Ar + + O + + O, is the most intense channel following interactions of Ar 2+ with O2, in agreement with previous experiments. Many different combinations of Ar 2+ and product electronic states contribute to the product flux in this channel. Major dissociation pathways of the nascent O2 + * ion involve the ion's first and second dissociation limits. Unusually, the experimental results clearly show the involvement of a short-lived collision complex [ArO2 ] 2+ in this channel. The formation of O + and ArO + involves direct abstraction of O − from O2 by Ar 2+ . There is scant evidence of the involvement of a collision complex in this bond forming pathway. The ArO + product appears to be formed in the first excited electronic state ( 2 Π). The formation of O + + O + results from dissociative double electron transfer via an O2 2+ intermediate. The exoergicity of the dissociation of the nascent O2 2+ intermediate is in good agreement with previous work investigating the unimolecular dissociation of this dication.